2017
DOI: 10.1590/0103-8478cr20160643
|View full text |Cite
|
Sign up to set email alerts
|

Sealing type effect on corn silage quality in bunker silos

Abstract: Forage conservation in silos depends on the efficiency of silo sealing, among other factors, to minimize aerobic deterioration and consequent qualitative and quantitative losses in silage. Thus, the aim of the present study was to evaluate the effect of two sealing types on dry matter recovery rate, aerobic stability, nutritional composition, and in vitro digestibility of corn silage in bunker silos: 110-µm-thick double-sided polyethylene sealing (conventional sealing) and110-µm-thick double-sided polyethylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
1
7
1
2
Order By: Relevance
“…The feed out face of trench silos is the portion of the silo with the most challenging environment for silage preservation, due to the difficulty of compacting and sealing the site, so it is suggested that there is a greater influence of the type of sealing used, impacting on the quality of the fermentation process and consequently in the ruminal degradability of the material. Neumann et al (2017) evaluated the digestibility of corn silage dry matter under different types of sealing in trench silos, and reported no statistical difference between conventional and double sealing systems, differently from that found in this research, where the silage from the conventional sealing presented the lowest ruminal digestibility in relation to the types of sealing.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…The feed out face of trench silos is the portion of the silo with the most challenging environment for silage preservation, due to the difficulty of compacting and sealing the site, so it is suggested that there is a greater influence of the type of sealing used, impacting on the quality of the fermentation process and consequently in the ruminal degradability of the material. Neumann et al (2017) evaluated the digestibility of corn silage dry matter under different types of sealing in trench silos, and reported no statistical difference between conventional and double sealing systems, differently from that found in this research, where the silage from the conventional sealing presented the lowest ruminal digestibility in relation to the types of sealing.…”
Section: Resultscontrasting
confidence: 86%
“…In the same way, Junga and Trávnicek (2015) argued that the increase in temperature of the ensiled mass originates from the degradation of substrates, mainly by fungi and yeasts, which act in the presence of oxygen resulting in the elevation of the average pH values and lower nutritional value of the food due to aerobic deterioration. Neumann et al (2017), in a similar study, evaluated double sealing and conventional sealing, and reported average temperatures higher than those obtained in the present study (30.18 °C and 31.48 °C, respectively), and attributed the increase in silage temperature in the silo feed out face with the activity of aerobic spoilage microorganisms.…”
Section: Still According Tosupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, in Principal Component 2, the greatest influence on quality was the use of double-sided plastic film, which is related to silage storage. Double sealing did not affect the silage nutritional composition, but increased dry matter recovery (88.79% vs. 85.64%) and in vitro neutral detergent fiber digestibility (33.04% vs. 24.6%), when compared to the conventional version (NEUMANN et al, 2017). Figure 2.…”
Section: Principal Components Analysismentioning
confidence: 96%
“…Dessa forma, a obtenção de condições específicas para uma correta fermentação depende da manutenção de um ambiente anaeróbico no silo de armazenamento (Silva et al, 2015). Muitos fatores colaboram para a obtenção da anaerobiose, e a vedação do silo é essencial para preservar a massa ensilada, impedindo a entrada de ar e água que podem deteriorar a silagem, provocando o seu descarte (Neumann et al, 2017).…”
Section: Introductionunclassified